Energy-saving UHPC concrete and preparation method thereof
Through the preparation method of specific raw materials and the modified composite fiber reinforced fiber reinforcement of vinyl ester resin matrix, the microstructure and interface bonding strength of UHPC are optimized, and the problems of self-shrinkage and early cracking of UHPC are solved, which significantly improves its mechanical properties and durability.
Patent Information
- Application Number
- CN202411689766.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Ultra-high performance concrete (UHPC) has a large self-shrinkage phenomenon during condensation hardening and service, resulting in high risk of early cracking, affecting its promotion in engineering applications.
The preparation method for modifying composite fiber ribs with a specific proportion of raw materials and a unique vinyl ester resin matrix modified composite fiber ribs, including using KH550 modified glass microbeads, modified Elosite nanotubes, modified expanded vermiculite and vinyl ester resin matrix modified composite fiber ribs to optimize the microstructure and interface bonding strength of concrete.
It significantly reduces the risk of self-shrinkage and early cracking of UHPC, improves its compressive strength, flexural strength and fracture toughness, extends the service life of concrete, and gives it a wide range of application prospects in construction projects, bridge projects, tunnels and underground projects.
Smart Images

Figure BDA0005150621000000141 
Figure BDA0005150621000000151 
Figure BDA0005150621000000161
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of concrete, and in particular to an energy-saving UHPC concrete and a preparation method thereof. Background Art
[0002] Ultra-high performance concrete (UHPC) is a cement-based composite material with the characteristics of high strength, high toughness and low porosity. Its mechanical and durability properties far exceed those of ordinary concrete (NSC) and high-performance concrete (HPC), and its compressive strength and flexural strength are excellent. For this reason, it is widely used in many fields such as construction engineering, bridge engineering, tunnel and underground engineering. However, UHPC is not perfect. Due to its low water-cement ratio, high cementitious material content, high active mineral admixture content and low coarse aggregate content, it will experience large autogenous shrinkage during coagulation and hardening and service. The autogenous shrinkage accounts for more than 80% of the total shrinkage, which greatly increases the problem of early cracking of concrete and becomes one of the key technical problems that restrict the further promotion of UHPC in engineering applications. In addition, the shrinkage cracking of concrete allows corrosive ions to penetrate into the interior, significantly reducing the mechanical strength and durability of concrete, accelerating the corrosion and aging of concrete structures, leading to premature deterioration and damage of building structures, and seriously affecting the practicality and safety of marine infrastructure. Summary of the invention
[0003] In order to solve at least one of the above technical problems, an ultra-high performance concrete with small shrinkage, low risk of early cracking and good corrosion resistance is developed. The present application provides an energy-saving UHPC concrete and a preparation method thereof.
[0004] In a first aspect, the present application provides an energy-saving UHPC concrete, wherein the concrete comprises the following raw materials by weight: 110-150 parts of silicate cement, 18-35 parts of fly ash, 20-30 parts of KH550 modified glass microspheres, 50-75 parts of vinyl ester resin matrix modified composite fiber bars, 20-38 parts of silica fume, 100-175 parts of fine sand, 30-70 parts of steel fiber, 4-9 parts of water reducer, and 25-45 parts of water; The vinyl ester resin matrix modified composite fiber reinforcement is prepared by modifying the composite fiber with a vinyl ester resin matrix; The method for preparing the vinyl ester resin matrix modified composite fiber reinforcement comprises the following steps: A1. Mix hydrogen-containing silicone oil and KH560 in a mass ratio of 1:1, add a solvent and a catalyst, stir, and perform an addition reaction to obtain organosilicon for later use; A2, mixing halloysite nanotubes with ethanol, and then adding hydrogenated silicone oil and ethyl silicate to mix well to obtain modified halloysite nanotubes; A3, mixing hydrogen-containing silicone oil with ethyl silicate, and dropping the mixture onto the surface of expanded vermiculite, expanding the mixture in a microwave oven, and then placing the mixture in a mixed solution of KOH and anhydrous ethanol for stirring, and mixing the mixture to obtain modified expanded vermiculite; A4, vinyl ester resin, cyclohexanone dibutyl peroxide paste, and cobalt naphthenate styrene liquid are mixed in a weight ratio of 100:(1-3):(0.5-1.5) to prepare a vinyl ester resin emulsion; A5, the vinyl ester resin emulsion of step A4, the organosilicon of step A1, the modified halloysite nanotubes of step A2 and the modified expanded vermiculite of step A3 are uniformly mixed in a weight ratio of 100:(5-10):(0.5-1):(0.5-1) to prepare a vinyl ester resin matrix; A6, impregnating the composite fiber into the vinyl ester resin matrix of step A5, pultruding, rib-forming, curing, and cutting to obtain the vinyl ester resin matrix modified composite fiber reinforcement; The composite fiber in step A6 is prepared by mixing polypropylene fiber and polyvinyl alcohol fiber in a weight ratio of 1:1.
[0005] By adopting the above technical scheme, the energy-saving UHPC concrete provided by the present application effectively improves the performance of concrete through the combination of raw materials in a specific proportion and a unique method for preparing a vinyl ester resin matrix modified composite fiber bar. In terms of raw materials, silicate cement, as the main cementitious material, works synergistically with fly ash to provide basic strength for concrete. KH550 modified glass microspheres can improve the internal structure of concrete and reduce the risk of shrinkage. Silica ash further fills the pores and enhances the density of concrete. Fine sand, as a fine aggregate, together with other components, forms a stable structure. Steel fibers can bridge cracks and transfer stress. The polypropylene fibers and polyvinyl alcohol fibers in the vinyl ester resin matrix modified composite fiber bars bear tensile force, delay the development of cracks, and the modification of the vinyl ester resin matrix makes the fibers better bonded to the concrete matrix, enhancing the anti-cracking effect. In terms of solving concrete corrosion and improving durability, when preparing the vinyl ester resin matrix modified composite fiber bars, the organosilicon generated by the reaction of hydrogenated silicone oil and KH560 in step A1 provides chemical stability and hydrophobicity. The modified halloysite nanotubes of step A2 and the modified expanded vermiculite of step A3 can form a physical barrier, fill pores, and reduce the channels of corrosive media. In step A4, vinyl ester resin, dibutyl peroxide cyclohexanone paste, and cobalt cyclohexane acid styrene liquid are mixed to form an emulsion, and the vinyl ester resin is cured to form a three-dimensional network structure to wrap the fiber. Its chemical corrosion resistance combined with the action of initiator and promoter ensures curing and isolates the erosion of corrosive media. At the same time, the water reducer reduces the water-cement ratio and reduces the transmission channel of corrosive media, thereby improving the corrosion resistance of fiber reinforced bars and the durability of concrete. These measures not only significantly improve the compressive strength, flexural strength and fracture toughness of UHPC, but also effectively reduce the risk of self-shrinkage and early cracking, and extend the service life of concrete, making it have broad application prospects in various fields such as construction engineering, bridge engineering, tunnels and underground engineering.
[0006] Optionally, the weight ratio of the halloysite nanotubes, ethanol, hydrogenated silicone oil and ethyl silicate in step A2 is 1:(50-100):1:(2-4).
[0007] By adopting the above technical scheme, the uniform dispersion of halloysite nanotubes in ethanol and the effective mixing with hydrogenated silicone oil and ethyl silicate are ensured to form stable modified halloysite nanotubes. This modification process significantly improves the dispersibility and interfacial bonding strength of halloysite nanotubes in the vinyl ester resin matrix, thereby enhancing the mechanical properties and durability of the composite material. The addition of modified halloysite nanotubes not only improves the microstructure of concrete and reduces the generation of micro defects, but also improves the density and crack resistance of concrete, effectively solving the problems of large self-shrinkage and high risk of early cracking of UHPC during coagulation, hardening and service. At the same time, the physical barrier effect of modified halloysite nanotubes also helps to reduce the penetration of corrosive media, further improving the corrosion resistance and overall performance of concrete.
[0008] Optionally, the weight ratio of hydrogenated silicone oil, ethyl silicate, expanded vermiculite, KOH and anhydrous ethanol in step A3 is (1-3):(3-9):(0.5-1):(50-100).
[0009] By adopting the above technical solution, the expanded vermiculite is effectively mixed with hydrogen silicone oil and ethyl silicate during the surface modification process to form a stable modified expanded vermiculite. This modification process significantly improves the dispersibility and stability of expanded vermiculite in the vinyl ester resin matrix, which not only optimizes the microstructure of concrete and reduces the generation of micro defects, but also improves the density and crack resistance of concrete, effectively solving the problems of large self-shrinkage and high risk of early cracking of UHPC during coagulation, hardening and service. At the same time, the physical barrier effect of modified expanded vermiculite also helps to reduce the penetration of corrosive media, further improves the corrosion resistance and overall performance of concrete, and extends the service life of concrete.
[0010] Optionally, the weight ratio of the composite fiber to the vinyl ester resin matrix in step A6 is (3.5-5):1.
[0011] By adopting the above technical scheme, the uniform distribution and full infiltration of the composite fibers in the vinyl ester resin matrix are ensured, forming a vinyl ester resin matrix modified composite fiber bar with excellent performance. This optimized ratio not only improves the tensile strength and corrosion resistance of the composite fiber bar, but also significantly enhances its interfacial bonding strength with the concrete matrix, thereby effectively delaying the development and penetration of cracks, and improving the compressive strength and fatigue resistance of concrete. The addition of composite fiber bars further optimizes the microstructure of concrete, reduces the generation of micro defects, improves the density and crack resistance of concrete, and effectively solves the problems of large self-shrinkage and high risk of early cracking of UHPC during coagulation, hardening and service. At the same time, the physical barrier effect of the composite fiber bars also helps to reduce the penetration of corrosive media, further improves the corrosion resistance and overall performance of concrete, and extends the service life of concrete.
[0012] Optionally, the weight ratio of the KH550 modified glass microspheres to the vinyl ester resin matrix modified composite fiber reinforcement is 1:(2.2-2.8).
[0013] By adopting the above technical solution, when the weight ratio of KH550 modified glass microspheres to the vinyl ester resin matrix modified composite fiber reinforcement is 1: (2.2-2.8), the uniform distribution and effective combination of KH550 modified glass microspheres in the vinyl ester resin matrix modified composite fiber reinforcement are ensured. This optimized ratio not only improves the dispersion and stability of glass microspheres in the matrix, but also significantly enhances the microstructure of concrete, reduces the generation of micro defects, and improves the compactness and crack resistance of concrete. The addition of KH550 modified glass microspheres further optimizes the mechanical properties of concrete, improves its compressive strength and flexural strength, while its surface modification treatment provides chemical stability and hydrophobicity, effectively reduces the penetration of moisture and other corrosive media, and improves the corrosion resistance and durability of concrete. This technical solution effectively solves the problems of large self-shrinkage and high risk of early cracking of UHPC during coagulation and hardening and service, prolongs the service life of concrete, and makes it have a wider application prospect in various fields such as construction engineering, bridge engineering, tunnel and underground engineering.
[0014] Optionally, the weight ratio of the KH550 modified glass microspheres to the vinyl ester resin matrix modified composite fiber reinforcement is 1:2.5.
[0015] Optionally, the diameter of the vinyl ester resin matrix modified composite fiber reinforcement is 5-10 mm.
[0016] By adopting the above technical solution, this optimized diameter range not only improves the tensile strength and corrosion resistance of the composite fiber reinforcement, but also significantly enhances its interfacial bonding strength with the concrete matrix, thereby effectively delaying the development and penetration of cracks and improving the stability of concrete. The moderate diameter of the composite fiber reinforcement can form an effective three-dimensional network structure in the concrete, further optimize the microstructure of the concrete, reduce the generation of micro defects, improve the density and crack resistance of the concrete, and effectively solve the problems of large self-shrinkage and high risk of early cracking of UHPC during the coagulation, hardening and service process. At the same time, the physical barrier effect of the composite fiber reinforcement also helps to reduce the penetration of corrosive media, further improves the corrosion resistance and overall performance of the concrete, and extends the service life of the concrete.
[0017] Optionally, the silicate cement is PO42.5 grade ordinary silicate cement.
[0018] Optionally, the solvent in step A1 is selected from ethanol; and the catalyst is selected from NaOH.
[0019] In a second aspect, the present application provides a method for preparing energy-saving UHPC concrete, comprising the following steps: S1, weighing each raw material according to a proportion; S2, mixing silicate cement, fly ash, KH550 modified glass microspheres, silica fume, fine sand and 75% of water to prepare a first mixture; S3, adding the remaining water and water reducing agent to the first mixture in step S2 to obtain a second mixture; S4, adding the steel fiber to the second mixture in step S2, mixing, and stirring to obtain a third mixture; S5, fixing the vinyl ester resin matrix modified composite fiber reinforcement on a mold, and pouring the third mixture in step S4 into the mold, vibrating and compacting it, and curing and molding it under set conditions to obtain the energy-saving UHPC concrete.
[0020] By adopting the above technical scheme, the preparation method provided by the present application ensures the uniform mixing and full reaction of each raw material, forming a dense and uniform concrete structure. This preparation method not only improves the compressive strength, flexural strength and fracture toughness of concrete, but also significantly reduces the risk of self-shrinkage and early cracking, and improves the corrosion resistance and durability of concrete. Specifically, the addition of KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars optimizes the microstructure of concrete, reduces the generation of micro defects, and improves the compactness and crack resistance of concrete. The name needs to be modified. The composite fiber bars form an effective three-dimensional mesh structure in the concrete, which enhances the tensile, bending, impact and fatigue resistance of the concrete. At the same time, the use of water reducers reduces the water-cement ratio, reduces the transmission channel of corrosive media, and further improves the corrosion resistance of concrete. These measures effectively solve the problems of large self-shrinkage and high risk of early cracking of UHPC during coagulation and hardening and service, extend the service life of concrete, and make it have a wider application prospect in various fields such as construction engineering, bridge engineering, tunnels and underground engineering.
[0021] Optionally, the curing and molding conditions in step S5 are: temperature 20-25° C., humidity ≥ 90%.
[0022] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The energy-saving UHPC concrete provided in this application effectively improves the performance of concrete through the combination of raw materials in a specific proportion and a unique method for preparing a vinyl ester resin matrix modified composite fiber bar. In terms of raw materials, silicate cement, as the main cementitious material, works synergistically with fly ash to provide basic strength for concrete. KH550 modified glass microspheres can improve the internal structure of concrete and reduce the risk of shrinkage. Silica ash further fills the pores and enhances the density of concrete. Fine sand, as a fine aggregate, together with other components, forms a stable structure. Steel fibers can bridge cracks and transfer stress. The polypropylene fibers and polyvinyl alcohol fibers in the vinyl ester resin matrix modified composite fiber bars bear tensile force and delay the development of cracks, and the modification of the vinyl ester resin matrix makes the fibers better bonded to the concrete matrix and enhances the anti-cracking effect. In terms of solving the corrosion of fiber-reinforced bars and improving durability, when preparing the vinyl ester resin matrix modified composite fiber bars, the organosilicon generated by the reaction of hydrogenated silicone oil and KH560 in step A1 provides chemical stability and hydrophobicity. The modified halloysite nanotubes of step A2 and the modified expanded vermiculite of step A3 can form a physical barrier, fill pores, and reduce the channels of corrosive media. In step A4, vinyl ester resin, dibutyl peroxide cyclohexanone paste, and cobalt cyclohexane acid styrene liquid are mixed to form an emulsion, and the vinyl ester resin is cured to form a three-dimensional network structure to wrap the fiber. Its chemical corrosion resistance combined with the action of initiator and promoter ensures curing and isolates the erosion of corrosive media. At the same time, the water reducer reduces the water-cement ratio and reduces the transmission channel of corrosive media, thereby improving the corrosion resistance of fiber reinforced bars and the durability of concrete. These measures not only significantly improve the compressive strength, flexural strength and fracture toughness of UHPC, but also effectively reduce the risk of self-shrinkage and early cracking, and extend the service life of concrete, making it have broad application prospects in various fields such as construction engineering, bridge engineering, tunnels and underground engineering.
[0023] 2. When the weight ratio of KH550 modified glass microspheres to the vinyl ester resin matrix modified composite fiber bars is 1:(2.2-2.8), the uniform distribution and effective combination of KH550 modified glass microspheres in the vinyl ester resin matrix modified composite fiber bars are ensured. This optimized ratio not only improves the dispersion and stability of glass microspheres in the matrix, but also significantly enhances the microstructure of concrete, reduces the generation of micro defects, and improves the compactness and crack resistance of concrete. The addition of KH550 modified glass microspheres further optimizes the mechanical properties of concrete, improves its compressive strength and flexural strength, while its surface modification treatment provides chemical stability and hydrophobicity, effectively reduces the penetration of moisture and other corrosive media, and improves the corrosion resistance and durability of concrete. This technical solution effectively solves the problems of large self-shrinkage and high risk of early cracking of UHPC during coagulation and hardening and service, prolongs the service life of concrete, and makes it have a wider application prospect in various fields such as construction engineering, bridge engineering, tunnel and underground engineering.
[0024] 3. The preparation method provided in this application ensures the uniform mixing and full reaction of each raw material, forming a dense and uniform concrete structure. This preparation method not only improves the compressive strength, flexural strength and fracture toughness of concrete, but also significantly reduces the risk of self-shrinkage and early cracking, and improves the corrosion resistance and durability of concrete. Specifically, the addition of KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars optimizes the microstructure of concrete, reduces the generation of micro defects, and improves the compactness and crack resistance of concrete. The composite fiber bars form an effective three-dimensional mesh structure in the concrete, which enhances the tensile, bending, impact and fatigue resistance of the concrete. At the same time, the use of water reducers reduces the water-cement ratio, reduces the transmission channel of corrosive media, and further improves the corrosion resistance of concrete. These measures effectively solve the problems of large self-shrinkage and high risk of early cracking of UHPC during coagulation and hardening and service, extend the service life of concrete, and make it have a wider application prospect in various fields such as construction engineering, bridge engineering, tunnels and underground engineering. DETAILED DESCRIPTION
[0025] The present application is further described in detail below with reference to the embodiments.
[0026] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.
[0027] Ultra-high performance concrete (UHPC) is a cement-based composite material with high strength, high toughness and low porosity. Its mechanical and durability properties far exceed those of ordinary concrete (NSC) and high performance concrete (HPC), and its compressive strength and flexural strength are excellent. For this reason, it is widely used in many fields such as construction engineering, bridge engineering, tunnel and underground engineering. However, UHPC is not perfect. Due to its low water-cement ratio, high cementitious material content, high active mineral admixture content and low coarse aggregate content, it will experience large autogenous shrinkage during coagulation and hardening and service. The autogenous shrinkage accounts for more than 80% of the total shrinkage, which greatly increases the possibility of early cracking and becomes one of the key technical problems that restrict the further promotion of UHPC in engineering applications. In addition, the shrinkage cracking of concrete allows corrosive ions to penetrate into the interior, significantly reducing the mechanical strength and durability of concrete, accelerating the corrosion and aging of concrete structures, leading to premature deterioration and damage of building structures, and seriously affecting the practicality and safety of marine infrastructure. Therefore, in order to solve at least one of the above technical problems, the inventors of the present application have developed an ultra-high performance concrete with small shrinkage, low risk of early cracking and good corrosion resistance. The present application provides an energy-saving UHPC concrete and a preparation method thereof. In the first aspect, the present application provides an energy-saving UHPC concrete, the concrete comprising the following raw materials in parts by weight: 110-150 parts of silicate cement, 18-35 parts of fly ash, 20-30 parts of KH550 modified glass microspheres, 50-75 parts of vinyl ester resin matrix modified composite fiber bars, 20-38 parts of silica ash, 100-175 parts of fine sand, 30-70 parts of steel fibers, 4-9 parts of water reducer, and 25-45 parts of water. The composite fiber bars modified by the vinyl ester resin matrix are obtained by modifying the composite fibers by a vinyl ester resin matrix. The preparation method of the composite fiber bars modified by the vinyl ester resin matrix comprises the following steps: A1. Mix hydrogen-containing silicone oil and KH560 in a mass ratio of 1:1, add a solvent and a catalyst, stir, and perform an addition reaction to obtain organosilicon for later use; A2, mixing halloysite nanotubes with ethanol, and then adding hydrogenated silicone oil and ethyl silicate to mix well to obtain modified halloysite nanotubes; A3, mixing hydrogen-containing silicone oil with ethyl silicate, and dropping the mixture onto the surface of expanded vermiculite, expanding the mixture in a microwave oven, and then placing the mixture in a mixed solution of KOH and anhydrous ethanol for stirring, and mixing the mixture to obtain modified expanded vermiculite; A4, vinyl ester resin, cyclohexanone dibutyl peroxide paste, and cobalt naphthenate styrene liquid are mixed in a weight ratio of 100:(1-3):(0.5-1.5) to prepare a vinyl ester resin emulsion; A5, mixing the vinyl ester resin emulsion, silicone, modified halloysite nanotubes and modified expanded vermiculite in a weight ratio of 100:(5-10):(0.5-1):(0.5-1) to obtain a vinyl ester resin matrix; A6. The composite fiber is impregnated in a vinyl ester resin matrix, and then pultruded, rib-wrapped, cured, and cut to obtain a vinyl ester resin matrix modified composite fiber bar; the composite fiber is prepared by mixing polypropylene fiber and polyvinyl alcohol fiber in a weight ratio of 1:1. The energy-saving UHPC concrete provided in this application effectively improves the performance of concrete by matching raw materials in a specific proportion and a unique method for preparing a vinyl ester resin matrix modified composite fiber bar. In terms of raw materials, silicate cement, as the main cementitious material, works synergistically with fly ash to provide basic strength for concrete. KH550 modified glass microspheres can improve the internal structure of concrete and reduce the risk of shrinkage. Silica ash further fills pores and enhances the density of concrete. Fine sand, as a fine aggregate, together with other components, forms a stable structure. Steel fibers can bridge cracks and transfer stress. The polypropylene fibers and polyvinyl alcohol fibers in the vinyl ester resin matrix modified composite fiber bars bear the tensile force, delaying the development of cracks, and the modification of the vinyl ester resin matrix makes the fiber better bonded to the concrete matrix, enhancing the anti-cracking effect. In terms of solving the corrosion of fiber reinforced bars and improving durability, when preparing the composite fiber reinforced bars modified by vinyl ester resin matrix, the organic silicon generated by the reaction of hydrogenated silicone oil and KH560 in step A1 provides chemical stability and hydrophobicity. The modified halloysite nanotubes in step A2 and the modified expanded vermiculite in step A3 can form a physical barrier, fill pores, and reduce the channels of corrosive media. In step A4, vinyl ester resin, dibutyl peroxide cyclohexanone paste, and cobalt cyclohexane acid styrene liquid are mixed to form an emulsion. The vinyl ester resin is cured to form a three-dimensional network structure to wrap the fiber. Its chemical corrosion resistance is combined with the initiator and accelerator to ensure curing and isolate the erosion of corrosive media. At the same time, the water reducer reduces the water-binder ratio and reduces the transmission channel of corrosive media, thereby improving the corrosion resistance of fiber reinforced bars and the durability of concrete. These measures not only significantly improve the compressive strength, flexural strength and fracture toughness of UHPC, but also effectively reduce the risk of self-shrinkage and early cracking, extend the service life of concrete, and make it have broad application prospects in various fields such as construction engineering, bridge engineering, tunnels and underground engineering.
[0028] In some embodiments, the weight ratio of the halloysite nanotubes, ethanol, hydrogenated silicone oil and ethyl silicate in step A2 is 1:(50-100):1:(2-4).
[0029] Exemplarily, the weight ratio of the halloysite nanotubes, ethanol, hydrogenated silicone oil and ethyl silicate in step A2 is 1:50:1:2, 1:75:1:3, 1:100:1:4 or a range consisting of any two of the above values. Based on the above ratio, the present application ensures the uniform dispersion of the halloysite nanotubes in ethanol and the effective mixing with the hydrogenated silicone oil and ethyl silicate to form stable modified halloysite nanotubes. This modification process significantly improves the dispersibility and interfacial bonding strength of the halloysite nanotubes in the vinyl ester resin matrix, thereby enhancing the mechanical properties and durability of the composite material. The addition of modified halloysite nanotubes not only improves the microstructure of the concrete and reduces the generation of micro-defects, but also improves the compactness and crack resistance of the concrete, effectively solving the problems of large self-shrinkage and high risk of early cracking of UHPC during coagulation, hardening and service. At the same time, the physical barrier effect of the modified halloysite nanotubes also helps to reduce the penetration of corrosive media, further improving the corrosion resistance and overall performance of the concrete.
[0030] In some embodiments, the weight ratio of hydrogenated silicone oil, ethyl silicate, expanded vermiculite, KOH and anhydrous ethanol in step A3 is (1-3):(3-9):(0.5-1):(50-100).
[0031] Exemplarily, the weight ratio of hydrogen-containing silicone oil, ethyl silicate, expanded vermiculite, KOH and anhydrous ethanol in step A3 is 1:3:0.5:50, 2:7:0.8:80, 3:9:1:100 or a range consisting of any two of the above values. Based on the above ratio, the present application ensures the effective mixing of expanded vermiculite with hydrogen-containing silicone oil and ethyl silicate during the surface modification process to form a stable modified expanded vermiculite. This modification process significantly improves the dispersibility and stability of expanded vermiculite in the vinyl ester resin matrix, thereby not only optimizing the microstructure of concrete and reducing the generation of micro-defects, but also improving the density and crack resistance of concrete, effectively solving the problems of large self-shrinkage and high risk of early cracking of UHPC during coagulation, hardening and service. At the same time, the physical barrier effect of the modified expanded vermiculite also helps to reduce the penetration of corrosive media, further improves the corrosion resistance and overall performance of concrete, and extends the service life of concrete.
[0032] In some embodiments, the weight ratio of the composite fiber to the vinyl ester resin matrix in step A6 is (3.5-5):1.
[0033] Exemplarily, the weight ratio of the composite fiber to the vinyl ester resin matrix in step A6 is 3.5:1, 4.5:1, 5:1 or a range consisting of any two of the above values. Based on the above ratio, the present application ensures the uniform distribution and full infiltration of the composite fiber in the vinyl ester resin matrix, forming a vinyl ester resin matrix modified composite fiber bar with excellent performance. This optimized ratio not only improves the tensile strength and corrosion resistance of the composite fiber bar, but also significantly enhances its interfacial bonding strength with the concrete matrix, thereby effectively delaying the development and penetration of cracks, and improving the tensile, bending, impact and fatigue resistance of the concrete. The addition of composite fiber bars further optimizes the microstructure of the concrete, reduces the generation of micro defects, improves the compactness and crack resistance of the concrete, and effectively solves the problems of large self-shrinkage and high risk of early cracking of UHPC during coagulation, hardening and service. At the same time, the physical barrier effect of the composite fiber bars also helps to reduce the penetration of corrosive media, further improves the corrosion resistance and overall performance of the concrete, and extends the service life of the concrete.
[0034] In some embodiments, the weight ratio of KH550 modified glass microspheres to vinyl ester resin matrix modified composite fiber reinforcement is 1:(2.2-2.8).
[0035] Exemplarily, the weight ratio of KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars is 1:2.2, 1:2.6, 1:2.8 or a range consisting of any two of the above values. Based on the above ratio, when the weight ratio of KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars is 1:(2.2-2.8), the present application ensures the uniform distribution and effective combination of KH550 modified glass microspheres in the vinyl ester resin matrix modified composite fiber bars. This optimized ratio not only improves the dispersibility and stability of the glass microspheres in the matrix, but also significantly enhances the microstructure of the concrete, reduces the generation of micro defects, and improves the compactness and crack resistance of the concrete. The addition of KH550 modified glass microspheres further optimizes the mechanical properties of concrete, improves its compressive strength and flexural strength, and its surface modification treatment provides chemical stability and hydrophobicity, effectively reduces the penetration of moisture and other corrosive media, and improves the corrosion resistance and durability of concrete. This technical solution effectively solves the problems of large shrinkage and high risk of early cracking of UHPC during the solidification and hardening and service process, prolongs the service life of concrete, and gives it a wider application prospect in various fields such as construction engineering, bridge engineering, tunnel and underground engineering.
[0036] In some embodiments, the weight ratio of KH550 modified glass microspheres to vinyl ester resin matrix modified composite fiber reinforcement is 1:2.5.
[0037] In some embodiments, the diameter of the vinyl ester resin matrix modified composite fiber bar is 5-10 mm. This optimized diameter range not only improves the tensile strength and corrosion resistance of the composite fiber bar, but also significantly enhances its interfacial bonding strength with the concrete matrix, thereby effectively delaying the development and penetration of cracks and improving the stability of concrete. The composite fiber bar has a moderate diameter and can form an effective three-dimensional network structure in the concrete, further optimizing the microstructure of the concrete, reducing the generation of micro defects, improving the density and crack resistance of the concrete, and effectively solving the problems of large self-shrinkage and high risk of early cracking of UHPC during coagulation, hardening and service. At the same time, the physical barrier effect of the composite fiber bar also helps to reduce the penetration of corrosive media, further improving the corrosion resistance and overall performance of the concrete, and extending the service life of the concrete.
[0038] In some embodiments, the silicate cement is PO42.5 grade ordinary silicate cement.
[0039] In some embodiments, the solvent in step A1 is selected from ethanol; and the catalyst is selected from NaOH.
[0040] In a second aspect, the present application provides a method for preparing energy-saving UHPC concrete, comprising the following steps: S1, weighing each raw material according to a proportion; S2, mixing silicate cement, fly ash, KH550 modified glass microspheres, silica fume, fine sand and 75% of water to prepare a first mixture; S3, adding the remaining water and water reducing agent to the mixture in step S2 to obtain a second mixture; S4, adding the steel fiber to the second mixture, mixing, and stirring to obtain a third mixture; S5, fix the vinyl ester resin matrix modified composite fiber bar on the mold, and pour the third mixture described in step S4 into the mold, vibrate and compact, and after curing and molding under the set conditions, energy-saving UHPC concrete is obtained. The preparation method provided in this application ensures the uniform mixing and full reaction of each raw material, forming a dense and uniform concrete structure. This preparation method not only improves the compressive strength, flexural strength and fracture toughness of concrete, but also significantly reduces the risk of self-shrinkage and early cracking, and improves the corrosion resistance and durability of concrete. Specifically, the addition of KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars optimizes the microstructure of concrete, reduces the generation of micro defects, and improves the compactness and crack resistance of concrete. The vinyl ester resin matrix modified composite fiber bars form an effective three-dimensional mesh structure in concrete, which enhances the compressive strength of concrete, reduces early shrinkage and cracking. At the same time, the use of water reducer reduces the water-cement ratio, reduces the transmission channel of corrosive media, and further improves the corrosion resistance of concrete. These measures effectively solve the problems of large shrinkage and high risk of early cracking of UHPC during the solidification and hardening and service process, extend the service life of concrete, and give it a wider application prospect in various fields such as construction engineering, bridge engineering, tunnel and underground engineering.
[0041] In some embodiments, the curing and molding conditions in step S5 are: temperature 20-25° C., humidity ≥ 90%. Specific embodiments
[0042] All chemical components used in this application are commercially available unless otherwise specified.
[0043] Preparation Examples 1-3 provide vinyl ester resin matrix modified composite fiber reinforcement.
[0044] Preparation Example 1 This preparation example provides a vinyl ester resin matrix modified composite fiber tendon, and the preparation method comprises the following steps: A1, mixing hydrogen-containing silicone oil and KH560 in a mass ratio of 1:1, using ethanol as a solvent, and reacting at room temperature for 8 hours using a magnetic stirrer (200 r / min) under the catalytic effect of NaOH to obtain organic silicon for standby use; A2, mixing halloysite nanotubes with ethanol, and then adding hydrogenated silicone oil and ethyl silicate to mix well to obtain modified halloysite nanotubes; A3, mixing hydrogen-containing silicone oil with ethyl silicate, and dropping the mixture onto the surface of expanded vermiculite, expanding the mixture in a microwave oven, and then placing the mixture in a mixed solution of KOH and anhydrous ethanol for stirring, and mixing the mixture to obtain modified expanded vermiculite; A4, vinyl ester resin, cyclohexanone dibutyl peroxide paste, and cobalt naphthenate styrene liquid were mixed in a weight ratio of 100:1:0.5 to prepare a vinyl ester resin emulsion; A5, mixing the vinyl ester resin emulsion in step A4, the organosilicon in step A1, the modified halloysite nanotubes in step A2 and the modified expanded vermiculite in step A3 in a weight ratio of 100:5:0.5:0.5 to obtain a vinyl ester resin matrix; A6, impregnating the composite fiber into the vinyl ester resin matrix prepared in step A5, pultruding (pultrusion rate is 0.8 m / min), rib-forming, curing, and cutting to obtain a vinyl ester resin matrix modified composite fiber rib; The composite fiber in step A6 is prepared by mixing polypropylene fiber and polyvinyl alcohol fiber in a weight ratio of 1:1.
[0045] The weight ratio of the halloysite nanotubes, ethanol, hydrogenated silicone oil and ethyl silicate in step A2 is 1:50:1:2. The weight ratio of the hydrogenated silicone oil, ethyl silicate, expanded vermiculite, KOH and anhydrous ethanol in step A3 is 1:3:0.5:50. The weight ratio of the composite fiber and the vinyl ester resin matrix in step A6 is 3.5:1. The diameter of the vinyl ester resin matrix modified composite fiber tendon is 5-10 mm.
[0046] Preparation Example 2 This preparation example provides a vinyl ester resin matrix modified composite fiber tendon, and the preparation method comprises the following steps: A1, mixing hydrogen-containing silicone oil and KH560 in a mass ratio of 1:1, using ethanol as a solvent, and reacting at room temperature for 8 hours using a magnetic stirrer (200 r / min) under the catalytic effect of NaOH to obtain organic silicon for standby use; A2, mixing halloysite nanotubes with ethanol, and then adding hydrogenated silicone oil and ethyl silicate to mix well to obtain modified halloysite nanotubes; A3, mixing hydrogen-containing silicone oil with ethyl silicate, and dropping the mixture onto the surface of expanded vermiculite, expanding the mixture in a microwave oven, and then placing the mixture in a mixed solution of KOH and anhydrous ethanol for stirring, and mixing the mixture to obtain modified expanded vermiculite; A4, vinyl ester resin, cyclohexanone dibutyl peroxide paste, and cobalt naphthenate styrene liquid were mixed in a weight ratio of 100:1:1 to prepare a vinyl ester resin emulsion; A5, mixing the vinyl ester resin emulsion in step A4, the organosilicon in step A1, the modified halloysite nanotubes in step A2 and the modified expanded vermiculite in step A3 in a weight ratio of 100:8:0.8:0.9 to obtain a vinyl ester resin matrix; A6, impregnating the composite fiber into the vinyl ester resin matrix prepared in step A5, pultruding (pultrusion rate is 0.8 m / min), rib-forming, curing, and cutting to obtain a vinyl ester resin matrix modified composite fiber rib; The composite fiber in step A6 is prepared by mixing polypropylene fiber and polyvinyl alcohol fiber in a weight ratio of 1:1.
[0047] The weight ratio of the halloysite nanotubes, ethanol, hydrogenated silicone oil and ethyl silicate in step A2 is 1:85:1:3. The weight ratio of the hydrogenated silicone oil, ethyl silicate, expanded vermiculite, KOH and anhydrous ethanol in step A3 is 2:7:0.8:85. The weight ratio of the composite fiber and the vinyl ester resin matrix in step A6 is 4.5:1. The diameter of the vinyl ester resin matrix modified composite fiber tendon is 5-10 mm.
[0048] Preparation Example 3 This preparation example provides a vinyl ester resin matrix modified composite fiber tendon, and the preparation method comprises the following steps: A1, mixing hydrogen-containing silicone oil and KH560 in a mass ratio of 1:1, using ethanol as a solvent, and reacting at room temperature for 8 hours using a magnetic stirrer (200 r / min) under the catalytic effect of NaOH to obtain organic silicon for standby use; A2, mixing halloysite nanotubes with ethanol, and then adding hydrogenated silicone oil and ethyl silicate to mix well to obtain modified halloysite nanotubes; A3, mixing hydrogen-containing silicone oil with ethyl silicate, and dropping the mixture onto the surface of expanded vermiculite, expanding the mixture in a microwave oven, and then placing the mixture in a mixed solution of KOH and anhydrous ethanol for stirring, and mixing the mixture to obtain modified expanded vermiculite; A4, vinyl ester resin, cyclohexanone dibutyl peroxide paste, and cobalt naphthenate styrene liquid were mixed in a weight ratio of 100:1:1.5 to prepare a vinyl ester resin emulsion; A5, mixing the vinyl ester resin emulsion in step A4, the organosilicon in step A1, the modified halloysite nanotubes in step A2 and the modified expanded vermiculite in step A3 in a weight ratio of 100:10:1:1 to obtain a vinyl ester resin matrix; A6, impregnating the composite fiber into the vinyl ester resin matrix prepared in step A5, pultruding (pultrusion rate is 0.8 m / min), rib-forming, curing, and cutting to obtain a vinyl ester resin matrix modified composite fiber rib; The composite fiber in step A6 is prepared by mixing polypropylene fiber and polyvinyl alcohol fiber in a weight ratio of 1:1.
[0049] The weight ratio of the halloysite nanotubes, ethanol, hydrogenated silicone oil and ethyl silicate in step A2 is 1:100:1:4. The weight ratio of the hydrogenated silicone oil, ethyl silicate, expanded vermiculite, KOH and anhydrous ethanol in step A3 is 3:9:1:100. The weight ratio of the composite fiber and the vinyl ester resin matrix in step A6 is 5:1. The diameter of the vinyl ester resin matrix modified composite fiber rib is 5-10 mm.
[0050] Example 1 The present embodiment provides an energy-saving UHPC concrete, which includes the following raw materials by weight: 110 parts of Portland cement, 18 parts of fly ash, 28 parts of KH550 modified glass microspheres, 70 parts of vinyl ester resin matrix modified composite fiber reinforcement, 20 parts of silica fume, 100 parts of fine sand, 30 parts of steel fiber, 4 parts of water reducer, and 25 parts of water; The vinyl ester resin matrix modified composite fiber reinforcement in this embodiment is prepared from the vinyl ester resin matrix prepared in Preparation Example 1.
[0051] The silicate cement in this embodiment is PO42.5 grade ordinary silicate cement.
[0052] The water reducing agent used in this embodiment is a polycarboxylic acid water reducing agent with a solid content of 30%.
[0053] The KH550 modified glass microspheres are prepared by mixing KH550, ethanol and glass microspheres in a weight ratio of 1:50:10. The method is as follows: dissolving KH550 in ethanol and adding glass microspheres to mix to prepare a mixture; stirring the mixture evenly to ensure that KH550 is evenly attached to the surface of the glass microspheres; The mixture was dried to remove excess solvent and water, and then cooled to room temperature to obtain KH550 modified glass microspheres.
[0054] The energy-saving UHPC concrete preparation method provided in this embodiment comprises the following steps: S1. Weigh the raw materials according to the ratio; S2, mixing silicate cement, fly ash, KH550 modified glass microspheres, silica fume, fine sand and 75% of water to prepare a first mixture; S3, adding the remaining water and water reducing agent to the mixture in step S2 to obtain a second mixture; S4, adding the steel fiber to the second mixture, mixing, and stirring to obtain a third mixture; S5. Fix the vinyl ester resin matrix modified composite fiber reinforcement on the mold, and pour the third mixture in step S4 into the mold, vibrate and compact it, and after curing and molding at a temperature of 20-25° C. and a humidity of ≥95%, obtain energy-saving UHPC concrete.
[0055] Example 2 The difference between this embodiment and embodiment 1 is that, in this embodiment, when preparing energy-saving UHPC concrete, the total weight of KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars is 98 parts, wherein the weight ratio of KH550 modified glass microspheres to vinyl ester resin matrix modified composite fiber bars is 1:2.2.
[0056] Example 3 The difference between this embodiment and embodiment 1 is that, in this embodiment, when preparing energy-saving UHPC concrete, the total weight of KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars is 98 parts, wherein the weight ratio of KH550 modified glass microspheres to vinyl ester resin matrix modified composite fiber bars is 1:2.6.
[0057] Example 4 The difference between this embodiment and embodiment 1 is that, in this embodiment, when preparing energy-saving UHPC concrete, the total weight of KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars is 98 parts, wherein the weight ratio of KH550 modified glass microspheres to vinyl ester resin matrix modified composite fiber bars is 1:2.8.
[0058] Comparative Examples 1-6 Comparative Example 1 The difference between this comparative example and Example 1 is that when preparing energy-saving UHPC concrete, an equal amount of KH550 modified glass microspheres is used to replace the vinyl ester resin matrix modified composite fiber reinforcement.
[0059] Comparative Example 2 The difference between this comparative example and Example 1 is that when preparing energy-saving UHPC concrete, an equal amount of vinyl ester resin matrix modified composite fiber reinforcement is used to replace KH550 modified glass microspheres.
[0060] Comparative Example 3 The difference between this comparative example and Example 1 is that when preparing energy-saving UHPC concrete, an equal amount of composite fibers is used to replace the vinyl ester resin matrix modified composite fiber reinforcement.
[0061] Comparative Example 4 The difference between this comparative example and Example 1 is that when preparing energy-saving UHPC concrete, an equal amount of polypropylene fibers are used instead of composite fibers.
[0062] Comparative Example 5 The difference between this comparative example and Example 1 is that when preparing energy-saving UHPC concrete, an equal amount of polyvinyl alcohol fibers are used instead of composite fibers.
[0063] Comparative Example 6 The difference between this comparative example and Example 1 is that when preparing energy-saving UHPC concrete, an equal amount of unmodified glass microspheres are used instead of KH550 modified glass microspheres.
[0064] Control concrete (benchmark concrete): The control concrete is a concrete to which the vinyl ester resin matrix modified composite fiber reinforcement is not added when preparing the energy-saving UHPC concrete.
[0065] Experimental testing: Compressive strength test: refer to GB / T 17671-2021 for testing.
[0066] Shrinkage test: refer to GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" for shrinkage test (wrap the surface of the concrete sample with plastic wrap, then seal it with self-adhesive aluminum foil, and place the sealed specimen in an environment with a temperature of 20±1℃ and a relative humidity of 95% for curing for 28 days).
[0067] Crack resistance test: According to Appendix A of T / CECS10001-2017 "Anti-crack and anti-seepage composite materials for concrete", the crack reduction coefficient in the early crack resistance of concrete is determined; wherein the tested concrete is the concrete samples prepared in Examples 1-4 and Comparative Examples 1-6.
[0068] Corrosion resistance coefficient: refer to GB / T50082 concrete durability test method, prepare concrete test block: 100×100×100mm 3 After curing for 28 days under standard conditions of 20±2℃ and 95% humidity, immerse it in a composite brine simulated by natural saline water made of 1000ml pure water, 30g anhydrous sodium sulfate, 1.65g sodium chloride and 17.6g magnesium chloride heptahydrate for 6 hours, and dry it for 4 hours as one cycle. The ratio of the compressive strength after 100 cycles to the compressive strength before the durability test. Specifically as follows: Before the durability test (i.e. after 28 days of curing), the initial compressive strength of the concrete specimen is measured, recorded as R0. After 100 corrosion cycles, the compressive strength of the concrete specimen is measured again, recorded as Rf. Calculate the corrosion resistance coefficient: The calculation formula of the corrosion resistance coefficient K is: K=Rf / R0 The experimental test results of Examples 1-4 and Comparative Examples 1-6 are shown in Table 1.
[0069] Table 1 - Experimental test results of Examples 1-4 and Comparative Examples 1-6 Result analysis: The difference between Example 2-4 and Example 1 is that when preparing energy-saving UHPC concrete, the total weight of KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars remains unchanged, but the weight ratio between the two changes. Combined with the experimental test results in Table 1, it can be seen that when the weight ratio of KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars is 1:2.5, the energy-saving UHPC concrete prepared exhibits higher compressive strength, lower shrinkage and better corrosion resistance.
[0070] The difference between comparative example 1 and example 1 is that when preparing energy-saving UHPC concrete, an equal amount of KH550 modified glass microspheres are used to replace the vinyl ester resin matrix modified composite fiber bars. The results show that although the concrete has a certain compressive strength, the shrinkage rate is high and the corrosion resistance is poor. The difference between comparative example 2 and example 1 is that when preparing energy-saving UHPC concrete, an equal amount of vinyl ester resin matrix modified composite fiber bars are used to replace KH550 modified glass microspheres. The results show that although such concrete has a certain compressive strength, the shrinkage rate and corrosion resistance are not as good as those of example 1. Combining the experimental test data of comparative examples 1-2 and example 1, it can be seen that when KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars are used in combination, the compressive strength of energy-saving UHPC concrete can be significantly improved, the shrinkage rate can be reduced, and the corrosion resistance can be enhanced, so that it has a wider application prospect in various fields such as construction engineering, bridge engineering, tunnel and underground engineering. The reason is that KH550 modified glass microspheres can optimize the microstructure of concrete, reduce shrinkage risk, and improve density; while the vinyl ester resin matrix modified composite fiber reinforcement significantly enhances the mechanical properties and crack resistance of concrete through its three-dimensional network structure and excellent bonding performance, while providing additional corrosion protection. The compound use of these two materials achieves a complementary effect, which comprehensively improves the overall performance of concrete.
[0071] The difference between Comparative Example 3 and Example 1 is that when preparing energy-saving UHPC concrete, an equal amount of composite fibers is used to replace the vinyl ester resin matrix modified composite fiber bars. Combined with the experimental test results of Table 1, it can be seen that when unmodified composite fibers are used to prepare UHPC concrete, the concrete shrinkage rate will be higher, and the corrosion resistance will be poor, and the improvement of compressive strength will not be significant. The reason is that the dispersibility and interfacial compatibility of the unmodified composite fibers in concrete are poor, and they cannot form a good bond with the concrete matrix, thereby affecting the overall performance of the concrete. Specifically, the dispersion of the unmodified composite fibers in the concrete is uneven, and local aggregation is easily formed, resulting in uneven stress distribution inside the concrete, increasing the risk of self-shrinkage and early cracking. At the same time, the surface activity of the unmodified composite fibers is low, and a physical barrier cannot be effectively formed to reduce the penetration of corrosive media, resulting in a decrease in the corrosion resistance of the concrete. In addition, the interfacial bonding force between the unmodified composite fibers and the concrete matrix is weak, and stress cannot be effectively transferred, thereby limiting the improvement of the compressive strength of the concrete. In contrast, the vinyl ester resin matrix modified composite fiber reinforcement significantly improved the interfacial bonding strength between the fiber and the concrete matrix and optimized the microstructure of the concrete through the modification treatment of vinyl ester resin, thereby significantly improving the compressive strength of the concrete, reducing the shrinkage rate and enhancing the corrosion resistance.
[0072] The difference between Example 4 and Example 1 is that when preparing energy-saving UHPC concrete, an equal amount of polypropylene fiber is used instead of composite fiber; the difference between Example 5 and Example 1 is that an equal amount of polyvinyl alcohol fiber is used instead of composite fiber. Combining Table 1 and the experimental test results of Comparative Examples 4-5, it can be seen that when polypropylene fiber and polyvinyl alcohol fiber are used in combination in the preparation of energy-saving UHPC concrete, the comprehensive performance of energy-saving UHPC concrete can be significantly improved. The reason is that polypropylene fiber has high tensile strength and good dispersibility, can form an effective stress transfer network in concrete, and improve the compressive strength of concrete; while polyvinyl alcohol fiber has good toughness and bonding properties, can effectively inhibit the expansion of cracks, and improve the crack resistance and impermeability of concrete. When these two fibers are used in combination, their advantages complement each other, which not only significantly improves the mechanical properties of concrete, but also effectively reduces the shrinkage rate of concrete, reduces the risk of self-shrinkage and early cracking, and enhances the corrosion resistance of concrete, so that it has a wider application prospect in various fields such as construction engineering, bridge engineering, tunnel and underground engineering.
[0073] The difference between Comparative Example 6 and Example 1 is that, when preparing energy-saving UHPC concrete, an equal amount of unmodified glass microspheres is used instead of KH550 modified glass microspheres. Combined with the experimental test results in Table 1, it can be seen that when unmodified glass microspheres are used, the compressive strength of the concrete is reduced to a certain extent, and it has a higher shrinkage rate. The reason may be that the unmodified glass microspheres have poor dispersibility and interface compatibility in concrete, and cannot effectively improve the internal structure and micropore distribution of concrete, thereby affecting the density and mechanical properties of concrete. In addition, the surface activity of unmodified glass microspheres is low, and the self-shrinkage of concrete cannot be effectively reduced, resulting in more microcracks in the concrete during the hardening process, which increases the shrinkage rate. In contrast, the KH550 modified glass microspheres are surface modified to improve the interfacial bonding force with the concrete matrix and optimize the microstructure of the concrete, thereby significantly improving the compressive strength and crack resistance of the concrete and reducing the shrinkage rate. These improvements enable energy-saving UHPC concrete to have better comprehensive performance and longer service life in practical applications. In summary, this application Embodiment 5-6 The difference between Example 5-6 and Example 1 is that, when preparing energy-saving UHPC concrete, the weight proportions of some components are different. The difference is shown in Table 2.
[0074] Table 2 - Differences between Examples 5-6 and Example 2 The experimental test results of Examples 5-6 are shown in Table 3.
[0075] Table 3 - Experimental test results of Examples 5-6 Example Compressive strength (28d, Mpa) <![CDATA[28d shrinkage rate / *10 -6 > Crack reduction factor (%) Corrosion resistance factor Example 1 152.5 33 250 1.17 Example 5 154.9 26 266 1.19 Example 6 154.1 30 252 1.18 Result analysis: The difference between Example 5-6 and Example 1 is that when preparing energy-saving UHPC concrete, the weight proportions of some components are different. Combined with the experimental test results in Table 3, it can be seen that the comprehensive performance of the energy-saving UHPC concrete prepared by Example 5 is better.
[0076] Example 7 The difference between Examples 7-11 and Example 5 is that when preparing energy-saving UHPC concrete, based on the premise that the weight ratio of KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars is 1:2.5, the total weight ratio of KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars in the energy-saving UHPC concrete is changed, and a better weight ratio is selected.
[0077] In Example 5, the total weight of KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars is 95 parts, and the total weight of energy-saving UHPC concrete is 526 parts.
[0078] Therefore, it is not difficult to conclude that in Example 5, the proportion of KH550 modified glass microspheres (referred to as variable 1) and vinyl ester resin matrix modified composite fiber bars (referred to as variable 2) in the energy-saving UHPC concrete (referred to as the matrix) is 15.71%.
[0079] The differences between Examples 7-11 and Example 5 are shown in Table 4.
[0080] Proportion = (variable 1 + variable 2) / total weight of matrix * 100%.
[0081] Table 4 - Differences between Examples 7-11 and Example 5 The experimental test results of Examples 7-11 are shown in Table 5.
[0082] Table 5 - Experimental test results of Examples 7-11 Results analysis: The difference between Examples 7-11 and Example 5 is that when preparing energy-saving UHPC concrete, the total weight of KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars in the energy-saving UHPC concrete is different. Combined with the experimental test results in Table 5, it can be seen that when the total weight of KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars in the energy-saving UHPC concrete accounts for 13.77-16.64%, the comprehensive performance of the energy-saving UHPC concrete is better, and when the total weight of KH550 modified glass microspheres and vinyl ester resin matrix modified composite fiber bars in the energy-saving UHPC concrete accounts for 15.71%, the comprehensive performance of the energy-saving UHPC concrete is the best. When the proportion is too high or too low, the comprehensive performance will decrease.
[0083] Examples 12-13 Example 12 The difference between this embodiment and embodiment 5 is that when preparing energy-saving UHPC concrete, the preparation parameters of the vinyl ester resin matrix modified composite fiber reinforcement used are different. The vinyl ester resin matrix modified composite fiber reinforcement in this embodiment is prepared by Preparation Example 2.
[0084] Example 13 The difference between this embodiment and embodiment 5 is that when preparing energy-saving UHPC concrete, different preparation parameters of the vinyl ester resin matrix modified composite fiber reinforcement are used, and the vinyl ester resin matrix modified composite fiber reinforcement in this embodiment is prepared by Preparation Example 3. The experimental test results of embodiments 12-13 are shown in Table 6.
[0085] Table 6 - Experimental test results of Examples 12-13 Example Compressive strength (28d, Mpa) <![CDATA[28d shrinkage rate / *10 -6 > Crack reduction factor (%) Corrosion resistance factor Example 5 154.9 26 266 1.19 Example 12 155.5 23 271 1.21 Example 13 155.1 25 268 1.20 Result analysis: The difference between Example 12-13 and Example 5 is that different preparation parameters of the vinyl ester resin matrix modified composite fiber reinforcement are used in preparing energy-saving UHPC concrete. Combined with the experimental test results in Table 6, it can be seen that the energy-saving UHPC concrete prepared by Example 12 has better comprehensive performance.
[0086] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. An energy-saving UHPC concrete, characterized in that: The concrete comprises the following raw materials by weight: 110-150 parts of Portland cement, 18-35 parts of fly ash, 20-30 parts of KH550 modified glass microspheres, 50-75 parts of vinyl ester resin matrix modified composite fiber reinforcement, 20-38 parts of silica fume, 100-175 parts of fine sand, 30-70 parts of steel fiber, 4-9 parts of water reducer, and 25-45 parts of water; The vinyl ester resin matrix modified composite fiber reinforcement is prepared by modifying the composite fiber with a vinyl ester resin matrix; The method for preparing the vinyl ester resin matrix modified composite fiber reinforcement comprises the following steps: A1. Mix hydrogen-containing silicone oil and KH560 in a mass ratio of 1:1, add a solvent and a catalyst, stir, and perform an addition reaction to obtain organosilicon for later use; A2, mixing halloysite nanotubes with ethanol, and then adding hydrogenated silicone oil and ethyl silicate to mix well to obtain modified halloysite nanotubes; A3, mixing hydrogen-containing silicone oil with ethyl silicate, and dropping the mixture onto the surface of expanded vermiculite, expanding the mixture in a microwave oven, and then placing the mixture in a mixed solution of KOH and anhydrous ethanol for stirring, and mixing the mixture to obtain modified expanded vermiculite; A4, vinyl ester resin, cyclohexanone dibutyl peroxide paste, and cobalt naphthenate styrene liquid are mixed in a weight ratio of 100:(1-3):(0.5-1.5) to prepare a vinyl ester resin emulsion; A5, the vinyl ester resin emulsion of step A4, the organosilicon of step A1, the modified halloysite nanotubes of step A2 and the modified expanded vermiculite of step A3 are uniformly mixed in a weight ratio of 100:(5-10):(0.5-1):(0.5-1) to prepare a vinyl ester resin matrix; A6, impregnating the composite fiber into the vinyl ester resin matrix of step A5, pultruding, rib-forming, curing, and cutting to obtain the vinyl ester resin matrix modified composite fiber reinforcement; The composite fiber in step A6 is prepared by mixing polypropylene fiber and polyvinyl alcohol fiber in a weight ratio of 1:
1.
2. The energy-saving UHPC concrete according to claim 1, characterized in that: The weight ratio of the halloysite nanotubes, ethanol, hydrogenated silicone oil and ethyl silicate in step A2 is 1:(50-100):1:(2-4).
3. The energy-saving UHPC concrete according to claim 1, characterized in that: The weight ratio of hydrogenated silicone oil, ethyl silicate, expanded vermiculite, KOH and anhydrous ethanol in step A3 is (1-3):(3-9):(0.5-1):(50-100).
4. The energy-saving UHPC concrete according to claim 1, characterized in that: The weight ratio of the composite fiber to the vinyl ester resin matrix in step A6 is (3.5-5):
1.
5. The energy-saving UHPC concrete according to claim 1, characterized in that: The weight ratio of the KH550 modified glass microspheres to the vinyl ester resin matrix modified composite fiber reinforcement is 1:(2.2-2.8).
6. The energy-saving UHPC concrete according to claim 5, characterized in that: The weight ratio of the KH550 modified glass microspheres to the vinyl ester resin matrix modified composite fiber reinforcement is 1:2.
5.
7. The energy-saving UHPC concrete according to claim 1, characterized in that: The diameter of the vinyl ester resin matrix modified composite fiber reinforcement is 5-10 mm.
8. The energy-saving UHPC concrete according to claim 1, characterized in that: The silicate cement is PO42.5 grade ordinary silicate cement.
9. The energy-saving UHPC concrete according to claim 1, characterized in that: The solvent in step A1 is selected from ethanol; and the catalyst is selected from NaOH.
10. A method for preparing energy-saving UHPC concrete according to any one of claims 1 to 9, characterized in that: The steps include: S1. Weigh the raw materials according to the ratio; S2, mixing silicate cement, fly ash, KH550 modified glass microspheres, silica fume, fine sand and 75% of water to prepare a first mixture; S3, adding the remaining water and water reducing agent to the first mixture in step S2 to obtain a second mixture; S4, adding the steel fiber to the second mixture in step S2, mixing, and stirring to obtain a third mixture; S5, fixing the vinyl ester resin matrix modified composite fiber reinforcement on a mold, and pouring the third mixture in step S4 into the mold, vibrating and compacting it, and curing and molding it under set conditions to obtain the energy-saving UHPC concrete.
Citation Information
Patent Citations
UHPC (Ultra High Performance Concrete) board prepared from construction waste and preparation method of UHPC board
CN115611576A
High-crack-resistance low-shrinkage premixed concrete and preparation method thereof
CN116969725A
Waterproof impervious concrete and preparation method thereof
CN118529984A
Quick-drying high-early-strength concrete suitable for rapid repair of pavement slab and production method thereof
JP2022158954A
Sulfate corrosion-resistant concrete and method thereof for optimizing proportion and application
US20230129027A1